The cost of shopping: measuring virtual and physical access for obtaining goods - Chen, Jing; Cui, Mengying; Levinson, David (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The rise of e-commerce, bolstered by advancements in information and communication technology (ICT), has made it possible for consumers to shop online without the need to physically travel. The unexpected emergence of COVID-19 further accelerated this shift towards online shopping. This paper delves into the nuances of virtual versus physical access to goods, drawing from the dual access theory. It aims to offer a comprehensive understanding of the disparities in accessibility between digital and brick-and-mortar shopping experiences. Our results indicate that when considering the complete private costs—including the intrinsic costs of shopping and those incurred en route like travel and delivery fees—online shopping typically offers greater accessibility and is more cost-effective than its in-store counterpart. Interestingly, while physical access to shopping displays a pattern where the central city has a distinct advantage over the suburbs, virtual access presents a more uniform distribution throughout the city.